2014
DOI: 10.1007/s12098-014-1436-1
|View full text |Cite
|
Sign up to set email alerts
|

Isotonic Intravenous Maintenance Fluid Reduces Hospital Acquired Hyponatremia in Young Children with Central Nervous System Infections

Abstract: Administration of 0.9 % saline in 5 % dextrose as intravenous maintenance fluid in children with CNS infection leads to significantly less incidence of hyponatremia when compared to that with hypotonic fluids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…This age group has been excluded from most of the meta-analyses,14 18 19 the PIMS study16 and the paper by Pemde 17. The paper by Friedman with 110 children is the only study that included children of ≥1 month 15.…”
Section: Age Of the Childmentioning
confidence: 99%
“…This age group has been excluded from most of the meta-analyses,14 18 19 the PIMS study16 and the paper by Pemde 17. The paper by Friedman with 110 children is the only study that included children of ≥1 month 15.…”
Section: Age Of the Childmentioning
confidence: 99%
“…Additionally, obstructive hydrocephalus and < 3.5 years of age were identified as significant independent risk factors for severe hyponatremia among those affected. The risk for hospital-acquired hyponatremia and hyponatremic encephalopathy have been related to the use of hypotonic intravenous solutions [6,[70][71][72][73][74][75][76][77] . Wang et al [78] found a significantly higher risk for hyponatremia and severe hyponatremia among pediatric patients administered hypotonic solutions compared with isotonic fluids in a systematic review of ten randomized clinical trials involving 855 subjects.…”
Section: Childrenmentioning
confidence: 99%
“…Pulmonary infections are known to be associated with increased risk of hyponatremia [17][18][19][20]. Here, the authors bring forth a study comparing the risk of hyponatremia between hypotonic and isotonic PMS administered to children with very severe pneumonia admitted in the general pediatric ward.…”
Section: Introductionmentioning
confidence: 99%